(3GdMdd aj TQM CHjGJ GdLeds - (3YHO Gddg Hf eMeO Hf GdMSf GdHWdjhSis; (3YHO GdbGgQ Hf YHO GdQMef Hf eMeO GdLQLGfj, CHh HcQ,J (B471 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi YdefG eGde fcf fYde deG aQZJ ef GdcdGe ai GdMdd GdhGbY ai cJGH GdLed CQOJ Cf CJHY Pdc GdcdGe ai EYQGH HjGfg heYGfjgG s
(3BNQgG (B:s
(3hde jPcQ Hg GdaQROb hde CLO gPG ZdG ajeG WGdYJ ef TYQ GdaROb aCba efg Ydi MbjbI Je GdcJGH HMeO Gddg s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B48 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B310 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B606s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B602s
Keywords: (3GdCOHs